Knowledge and Opinions of Dental Practitioners for the Use of Artificial Intelligence (AI) in Dentistry: Artificial Intelligence in Dentistry - Islam, Sana Adeeba; Naz, Shikoh; Asim, Saima; Memon, Irtiza; Uqaili, Abdul Fatah; Pirzada, Samreen Ahmed (Pakistan Journal of Health Sciences, 2025)
Recent technological developments have paved the way for the application of Artificial Intelligence (AI) in dental care, offering improvements in diagnosis, treatment planning, and overall service delivery. Objective: To assess the level of awareness and perceptions of dental practitioners in Pakistan regarding the utilization of AI in clinical dentistry. Methods: A cross-sectional survey was executed between January and June 2024, encompassing 126 dental professionals. A structured questionnaire was shared via email and social media, gathering data on demographics, familiarity, and perspectives on AI in dentistry. Perceptions were measured using a 5-point Likert scale. Statistical analysis was performed using SPSS version 21.0, employing both descriptive and inferential methods. A p-value of <0.05 was considered statistically significant. Results: The average participant age was 41.14±13.76 years, with a predominance of female respondents (66.7%). A considerable portion (74.6%) reported familiarity with AI, while 77.8% were informed about its uses in dentistry. Although practical engagement was limited, 48% acknowledged AI's potential to enhance the field, while the same proportion expressed concerns over AI possibly replacing dental professionals. Enthusiasm toward AI was notable, with 55% showing interest. Many participants recognized AI's benefits in diagnostics and prognosis. Conclusions: Despite strong awareness and interest, the practical implementation of AI in dental practice remains low. Educational updates and supportive policies are essential to promote the integration of AI tools in clinical workflows.